Penerapan Metode Yanbu’a Dalam Meningkatkan Kualitas Membaca Al-Qur’an di Roudlotul Tarbiyatil Qur’an (RTQ) Ad Diin Kuwarasan, Kebumen - Aulia Hilda; Mustajab Mustajab (IAINU Kebumen, 2026)
This study aims to analyze the implementation of the Yanbu’a method in improving the qualityof Qur’anic reading at Roudlotul Tarbiyatil Qur’an (RTQ) Ad Diin, Kuwarasan, Kebumen. Theresearch focuses on three main aspects: (1) how the Yanbu’a method is implemented in Qur’aniclearning; (2) how students’ Qur’anic reading ability improves after its application; and (3) thesupporting and inhibiting factors affecting its implementation. This research employed aqualitative descriptive approach involving the caretakers, teachers, and students of RTQ Ad Diinas participants. Data were collected through observation, in-depth interviews, and documentation,and were analyzed through data reduction, data presentation, and conclusion drawing. Thefindings reveal that the Yanbu’a method is implemented through both classical and individual(sorogan) systems, systematically arranged from basic to advanced levels. This approacheffectively improves students’ reading abilities, especially in articulation accuracy, fluency, andtajwid application. Supporting factors include teacher competence, structured textbooks, andparental involvement, while constraints involve time limitations, varying student abilities, and anunbalanced teacher–student ratio. The study concludes that the Yanbu’a method is a systematic,effective, and contextually appropriate approach for Qur’anic learning in non-formal Islamicinstitutions, capable of enhancing reading quality while nurturing students’ spiritual disciplineand love for the Qur’an